Junior high school's EFL teachers' reading habits and literacy practices - Suwastini, Ni Komang Arie; Citrawati, Ni Kadek; Mahayanti, Ni Wayan Surya; Asril, Nice Maylani; Jayantini, I Gusti Agung Sri Rwa (UNIB Press, 2025)
As role models, teachers hold great potential to influence their student's literacy. The present study explored Indonesian teachers' reading habits and literacy practices. In this qualitative descriptive study, 75 EFL teachers from different provinces in Indonesia enrolled in the Kelas Kreatif Indonesia English Club and became respondents to the survey. The study employed questionnaires and interviews to collect data. The study revealed that regarding the frequency of reading, 36 teachers did not allocate exact time for reading, while 39 and 9 teachers allocated one and two hours a week, respectively. The teachers read a combination of material: online or printed textbooks/modules/articles, online/printed newspapers and magazines, and literary texts such as online/printed novels, short stories, and poems. They mostly read for professional and pleasure purposes, and a small number of teachers reads for test preparation. The teachers affect their students' literacy by promoting their students' reading habits by integrating various tasks that require reading and writing with opportunities for students to retell and share their reading results and writing products in open discussions. The teachers fostered the students' awareness of reading by giving reading tasks, sharing and discussing the reading experience, establishing literacy groups, forming reading corners, using the text or result of reading as learning resources, and posting the reading activities on social media. This study shows that teachers are potential influencers on the environment. Thus, further research should be conducted on the influence of reading habits on teachers' literacy performance on a larger scale.